Renal sonography in bipolar patients on long‐term lithium treatment. Issue 6 (18th February 2016) - Jończyk‐Potoczna, Katarzyna; Abramowicz, Maria; Chłopocka‐Woźniak, Maria; Strzelczuk‐Judka, Lidia; Michalak, Michał; Czekalski, Stanisław; Rybakowski, Janusz K.
ABSTRACT: Purpose: The aim of the study was to analyze sonographic (US) renal findings in lithium‐treated bipolar patients and to correlate them with renal function. Methods: Renal US and renal function tests were performed on 120 patients with bipolar disorder. Ninety patients (30 males, 60 females), aged 36–82 years, had received lithium therapy for an average of 16 years, whereas 30 patients (10 males, 20 females), aged 35–85 years, who had never been exposed to lithium, served as controls. Results: In the lithium‐treated group, patients with macrocysts (22%) had poorer renal function with higher creatinine serum concentrations, lower estimated glomerular filtration rates, and lower urine specific gravity, compared with the patients without macrocysts. The US changes characteristic for lithium nephropathy (punctate hyperechoic foci, microcysts < 2 mm, and increased echogenicity) were seen in three patients. These patients had been treated with lithium for more than 20 years and had impaired renal function. Sixteen percent of patients in the control group had macrocysts; however, no correlation between their presence and impaired renal function was found. Conclusions: The presence of macrocysts in the kidneys of lithium‐treated bipolar patients is associated with impaired renal function. The US changes characteristic for lithium nephropathy are rare, and in our study, were only found in patients treated with lithium for 20 years or more. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :354–359, 2016